Identifying Potential Clusters of Future Migration Associated With Water Stress in Africa: A Vulnerability Approach - de Bruin, Sophie Pieternel; Knoop, Joost; Visser, Hans; Biemans, Hester (Frontiers in Human Dynamics, 2022)
Decreasing yields due to water stress form a threat to rural livelihoods and can affect migration dynamics, especially in vulnerable regions that lack the capacity to adapt agriculture to water stress. But since migration is complex, non-linear and context-dependent, it is not feasible to predict the precise number of people that will migrate due to water stress. It is possible to map the different conditions that shape regional vulnerabilities and the number of people affected. This study presents a vulnerability approach to identify areas on the African continent where emigration associated with water stress is expected to be relatively high by 2050 under a middle-of-the-road scenario (SSP2) and compares the results with the 2010 situation. By utilizing among other indicators the water yield gap, the impact of water stress on rainfed agricultural crop yields is included, reflecting the impact of water stress on rural livelihoods depending on crop farming. The analysis was done on a water-province level, 393 in total. Clusters of potential emigration associated with the impacts of water stress on agriculture are projected for parts of the Sahel, the Horn of Africa and regions of Angola. The regions where migration associated with water stress is expected to be relatively high by 2050 are approximately the same as those of 2010, although more people are projected to be living in these water-stressed regions. By developing this vulnerability approach, this manuscript enlarges the current insights regarding future clusters of water stress-related migration.